Financial services and blockchain technology – current tax problems and challenges - Supera-Markowska, Maria (Journal of Finance and Financial Law, 2019)
Financial services due to the possibility of using virtual currencies (mainly bitcoins) for payments based on blockchain technology take on a new dimension. Making direct payments with the use of cryptocurrencies creates numerous tax-related issues, both in terms of acquiring and trading in virtual currencies, including in particular using them to perform the payment function, but also treating them as an investment or commercial activity. The issues related to this generate numerous tax challenges, both in the income tax system, as well as in turnover and property tax systems. These challenges, resulting from the need to determine the tax consequences of the use of blockchain technology in the financial services system for payments with cryptocurrencies, this paper has been devoted to.